Peningkatan Hasil Belajar Geografi Siswa Dengan Menggunakan Model Pembelajaran Connecting, Organizing, Reflecting, Extending Pada Materi Dinamika Hidrosfer Dan Dampaknya Terhadap Kehidupan Di Kelas X IIS 1 SMA Negeri 8 Kendari - Taufik Hidayat; Sitti Kasmiati; La Ode Nursalam (Jurnal Penelitian Pendidikan Geografi, 2022)
SMA Negeri 8 Kendari is one of the schools in Kendari City with low student learning outcomes. This study aims to describe student learning activities, teacher teaching activities, and student geography learning outcomes that are taught using the Connecting, Organizing, Reflecting, and Extending cooperative learning model. This type of research is Classroom Action Research conducted in two cycles, consisting of planning, implementation, observation, and reflection. The subjects of this research were 40 students of IIS 1 grade X of SMA Negeri 8 Kendari. The data in this study was obtained from observation sheets and learning outcomes tests. Based on the results of data analysis, it was found that: 1) in the first cycle the average score of student learning activities was 2,7 which was categorized as sufficiently increased in the second cycle to 3,4 which was categorized as good; 2) in the first cycle the average score of the teaching activities of the teachers was 2,6 which was categorized sufficiently increased in the second cycle to 3,5 which was categorized as good; and 3) an increase in Geography learning outcomes of students of class X IIS 1 of SMA Negeri 2 Kendari from cycle I to cycle II. The first cycle showed 24 students who scored 75 with an average value of 70. Furthermore, the results of the second cycle test showed a significant increase because 34 students scored 75 with an average score of 80.